Cereal-Legume Mixed Residue Addition Increases Yield and Reduces Soil Greenhouse Gas Emissions from Fertilized Winter Wheat in the North China Plain - Md Raseduzzaman; Gokul Gaudel; Md Razzab Ali; Arbindra Timilsina; Fiston Bizimana; Stephen Okoth Aluoch; Xiaoxin Li; Yuming Zhang; Chunsheng Hu (Agronomy, 2024)
Incorporating crop residues into the soil is an effective method for improving soil carbon sequestration, fertility, and crop productivity. Such potential benefits, however, may be offset if residue addition leads to a substantial increase in soil greenhouse gas (GHG) emissions. This study aimed to quantify the effect of different crop residues with varying C/N ratios and different nitrogen (N) fertilizers on GHG emissions, yield, and yield-scaled emissions (GHGI) in winter wheat. The field experiment was conducted during the 2018–2019 winter wheat season, comprising of four residue treatments (no residue, maize residue, soybean residue, and maize-soybean mixed residue) and four fertilizer treatments (control, urea, manure, and manure + urea). The experiment followed a randomized split-plot design, with N treatments as the main plot factor and crop residue treatments as the sub-plot factor. Except for the control, all N treatments received 150 kg N ha−1 season−1. The results showed that soils from all treatments acted as a net source of N2O and CO2 fluxes but as a net sink of CH4 fluxes. Soybean residue significantly increased soil N2O emissions, while mixed residue had the lowest N2O emissions among the three residues. However, all residue amendments significantly increased soil CO2 emissions. Furthermore, soybean and mixed residues significantly increased grain yield by 24% and 21%, respectively, compared to no residue amendment. Both soybean and mixed residues reduced GHGI by 25% compared to maize residue. Additionally, the urea and manure + urea treatments exhibited higher N2O emissions among the N treatments, but they contributed to significantly higher grain yields and resulted in lower GHGI. Moreover, crop residue incorporation significantly altered soil N dynamics. In soybean residue-amended soil, both NH4+ and NO3− concentrations were significantly higher (p < 0.05). Conversely, soil NO3− content was notably lower in the maize-soybean mixed residue amendment. Overall, our findings contribute to a comprehensive understanding of how different residue additions from different cropping systems influence soil N dynamics and GHG emissions, offering valuable insights into effective agroecosystems management for long-term food security and soil sustainability while mitigating GHG emissions.